2019
DOI: 10.1016/j.chembiol.2018.10.025
|View full text |Cite
|
Sign up to set email alerts
|

A Bump-Hole Approach for Directed RNA Editing

Abstract: Highlights d Bump-hole strategy developed for selective site-directed RNA editing (SDRE) system d SDRE in vitro and in human cells with bulky mutant ADAR2 proteins and guide RNAs d Directed editing on endogenous targets with reduced offtarget activity d Crystal structure of ADAR2-D E488Y with RNA duplex containing reduced abasic site

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 55 publications
0
33
0
Order By: Relevance
“…An advantage of this finding is that future experiments to evaluate rescue of Rett syndrome-like phenotypes in mice will result in lower levels of editase per cell because of peripheral virus delivery, which is necessary to infect the entire brain. Additionally, several groups are already beginning to identify editase molecules with higher specificity and efficiency ( Cox et al, 2017 ; Monteleone et al, 2019 ) for in vivo testing.…”
Section: Discussionmentioning
confidence: 99%
“…An advantage of this finding is that future experiments to evaluate rescue of Rett syndrome-like phenotypes in mice will result in lower levels of editase per cell because of peripheral virus delivery, which is necessary to infect the entire brain. Additionally, several groups are already beginning to identify editase molecules with higher specificity and efficiency ( Cox et al, 2017 ; Monteleone et al, 2019 ) for in vivo testing.…”
Section: Discussionmentioning
confidence: 99%
“…However, these mutant ADAR versions could lead to significant off-target effects. To mitigate this risk, Monteleone et al showed that they were able to reduce the off-target effects by mutating ADAR2 and altering the guide RNA [ 81 ]. Vallecillo-Viejo et al also showed that the off-target effects could be reduced when artificial versions of ADAR were targeted to the nucleus (through attaching several NLS to the artificial ADAR) [ 82 ].…”
Section: Suppression Of Nonsense Mutations: Approaches and Challenmentioning
confidence: 99%
“…Our case is likely the worst case scenario because we injected directly into hippocampus a very high titer of virus, and systemic injections, required for behavioral analysis in Rett mouse models, will result in much lower expression of Editase/cell. Several groups are already beginning to identify Editase molecules with higher specificity and efficiency [17,49], which will need to be tested in vivo, and the Rett mouse models will again be ideal for determining phenotypes. Importantly, despite the off-target events, in the mice expressing Editase and Mecp2 targeting guide, we observed mean editing rates of 50% at the target adenosines in Mecp2 RNA, in three different hippocampal neuronal fields containing multiple neuronal types [50][51][52][53][54] (Figure 2b).…”
Section: Discussionmentioning
confidence: 99%